Small religious images as instruments of social interaction. An analysis of holy cards based on a Căpleni collection - Szikszai, Mária (Swedish Journal of Romanian Studies, 2025)
This study analyzes a collection of 245 small holy cards preserved in a private collection in Căpleni (Romania). The primary aim is to explore the origins, functions, and connections of these holy cards with local religious societies. By focusing on the personal inscriptions and messages on these images, the research seeks to uncover how they were used and how they contributed to shaping interpersonal relationships. The methodology involves categorizing the items based on their usage occasions and the nature of their inscriptions, prioritizing qualitative aspects. The study employs theoretical frameworks such as the concepts of social objects and object biographies, to interpret the functions and social significance of the images. The findings reveal that these small religious images served not only devotional purposes but also acted as social catalysts that facilitated the maintenance and reinforcement of relationships within the community. The gifting and exchange of holy cards were embedded in social interactions, often accompanied by personal messages that documented and strengthened social bonds. These practices contributed to the reproduction of social capital by continuously reaffirming mutual recognition and obligations among community members. In conclusion, the study highlights the multifaceted roles of small devotional images as instruments of both personal piety and social connectivity. The analysis underscores the importance of considering the social life of objects to fully appreciate their cultural and anthropological significance within a given community.